Ultra-fast spin-mixing in a diketopyrrolopyrrole monomer/fullerene blend charge transfer state. Issue 46 (14th November 2017) - Salvadori, Enrico; Luke, Nathaniel; Shaikh, Jordan; Leventis, Anastasia; Bronstein, Hugo; Kay, Christopher W. M.; Clarke, Tracey M.
Abstract : Transient absorption and time-resolved EPR spectroscopy show an ultra-fast spin-mixing CT state in a small diketopyrrolopyrrole-based molecule blended with fullerene. Abstract : Diketopyrrolopyrrole (DPP) is one of the most common building blocks for small molecules and conjugated polymers designed for organic electronic applications. By attaining a detailed understanding of the photophysical behaviour for a simple DPP-based molecule in fullerene blends, we establish a foundation for spectroscopic investigations into more complex DPP-based systems. Transient absorption spectroscopy (TAS) and time-resolved electron paramagnetic resonance (TR-EPR) spectroscopy are used to examine bulk heterojunction blend films of a small diketopyrrolopyrrole-based molecule, 2, 5-bis(2-hexyldecyl)-3, 6-di(thiophen-2-yl)-2, 5-dihydropyrrolo[3, 4- c ]pyrrole-1, 4-dione (TDPP) with the common fullerene derivatives [6, 6]-phenyl-C61 -butyric acid methyl ester (PC60 BM) and [6, 6]-phenyl-C71 -butyric acid methyl ester (PC70 BM). Following pulsed laser excitation, the spectral signatures of a fullerene anion and a TDPP triplet state are observed on the picosecond timescale by TAS. The presence of these species implies the formation of a TDPP:PCBM charge transfer state that subsequently undergoes ultra-fast spin-mixing and geminate recombination to produce a TDPP triplet state. The overall photophysical mechanism is confirmed by TR-EPR spectroscopy, which unambiguously shows that the TDPP triplet is formed via spin-mixing in the TDPP:PCBM charge transfer state, rather than direct intersystem crossing from the excited singlet state.